Use of Farmyard Manure on Mixed Pasture of Guine Grass (Panicum Maximum) and Stylo (Stylo Guianensis) - Ali, Ahmed Sied (2004)
A field experiment was carried out to investigate the contribution of farmyard manure (FYM) in sustaining productivity and quality of Guinea-Stylo pasture under tin-mine slightly acidic soil at the Faculty of Agriculture research site, Universiti Putra Malaysia (UPM). The aim of this study was to evaluate the effect of rates of FYM on the physiology, dry matter (DM) yield, nutrient quality, and some soil physico-chemical properties in Guinea (Panicum maximum cv. Green panic) and Stylo (Stylosanthes guianensis cv. Pauciflora) mixed pasture. Six levels of FYM (0 (control), 10, 20, 30, 40, 50 t FYMlha), and inorganic fertilizer (50 kg P and 50 kg m a ) , were evaluated in a randomized complete block design with four replications. Guinea was transplanted from rootstocks, while Stylo seeds were sown between rows of Guinea grass at a seeding rate of 2 kglha. Four cuttings were taken at 5 weeks interval and compared for plant height, leaf: stem ratio (LSR) and DM yield. The first and the fourth cuttings were compared for plant height, photosynthetic rate (PR), leaf area index (LAI), stomatal conductance (SC), biomass yield, LSR, crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of both species. Beside plant analysis, some soil physical and chemical properties were measured at the first and the fourth cuttings. Application of FYM up to the rate of 50 tfha resulted significantly in higher vegetative growth of Guinea and increased rates of physiological processes compared to the control during the first and from that of inorganic fertilizer during the fourth cut. There was a significant increase in plant height, DM, CP, PR, LA1 and SC of Guinea grass with increasing rates of FYM applied. On the other hand, the DM yields and stomatal conductance of Stylo declined with increasing FYM rates of application. Increasing rates of FYM application significantly reduced the fiber content of both species. There was a significant linear decrease in NDF and ADF content of Guinea grass as well as Stylo with increasing rate of FYM applied. However, there was an increasing trend in fiber content of both species fiom the first cut to the fourth cut. In addition to its contribution on fodder productivity and quality, effects of FYM on soil physical and chemical properties were also evaluated. Soil analysis after the fmt and the fourth cut showed that application of FYM significantly decreased soil bulk density. Application of FYM up to 50 tlha also improved water retention characteristics, available water holding capacity, aggregation and aggregate stability of the soil, especially at the depth of 0-15 cm. However, application of inorganic fertilizer did not show a significant improvement in soil physical properties. Beside the effects of FYM on soil physical properties, its contribution on some soil chemical properties was also evaluated. The pH of manure amended soil was significantly higher than that of the control as well as from soil which received inorganic fertilizer, and the effect persisted up to the fourth cuttings. There was a significant linear increase in soil organic matter, nitrogen, phosphorus, potassium, calcium, and magnesium with increasing rate of FYM applied. The results of this study indicated that FYM up to 50 t/ha can be applied to improve the fertility of the soil and productivity as well as nutrient quality of Guinea grass-Stylo mixed pasture.